2011
DOI: 10.1097/mpa.0b013e3182200201
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence In Situ Hybridization and K-ras Analyses Improve Diagnostic Yield of Endoscopic Ultrasound-Guided Fine-Needle Aspiration of Solid Pancreatic Masses

Abstract: Combining routine cytology with FISH and K-ras analyses improves diagnostic yield of EUS-FNA of solid pancreatic masses. We propose to include these ancillary tests in the workup of atypical cytology from pancreatic EUS-FNA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 35 publications
0
30
0
Order By: Relevance
“…[232425] The majority of studies involving KRAS mutations have investigated their relationship with pancreatic adenocarcinoma[26272829] and genetic progression in pancreatic duct lesions and intraductal papillary mucinous neoplasms (IPMN). [303132] KRAS mutational analysis of pancreatic juice has even been used as a potential method for the early diagnosis of pancreatic carcinoma.…”
Section: Molecular Analysis Of Duct Stricture Brushing Specimensmentioning
confidence: 99%
See 3 more Smart Citations
“…[232425] The majority of studies involving KRAS mutations have investigated their relationship with pancreatic adenocarcinoma[26272829] and genetic progression in pancreatic duct lesions and intraductal papillary mucinous neoplasms (IPMN). [303132] KRAS mutational analysis of pancreatic juice has even been used as a potential method for the early diagnosis of pancreatic carcinoma.…”
Section: Molecular Analysis Of Duct Stricture Brushing Specimensmentioning
confidence: 99%
“…[303132] KRAS mutational analysis of pancreatic juice has even been used as a potential method for the early diagnosis of pancreatic carcinoma. [333435] Although KRAS mutations can be found in pre-invasive dysplastic lesions and invasive carcinomas of the pancreas,[2324252627282930] several studies have shown that KRAS mutation analysis is a sensitive test for pancreatic adenocarcinoma. [363738] Sturm et al .…”
Section: Molecular Analysis Of Duct Stricture Brushing Specimensmentioning
confidence: 99%
See 2 more Smart Citations
“…We are of the opinion that a larger and multicenter patient population could elucidate further the EUS features of pNETs and we believe that a confirmation of our original data could increase the clinical relevance of this set of observations. Over and above the pNETs ultrasonographic characteristics observed through EUS, such a sensitive and specific investigation also represents a reliable and effective support for performing a lesion biopsy, with an obvious subsequent clinically relevant impact in terms of diagnostic characterization, pathogenetic definition, and prognosis of the pNET [25-27]. Moreover, EUS can also be associated to radiofrequency ablation of pancreatic tumors, including those of neuroendocrine origin [28].…”
Section: Discussionmentioning
confidence: 99%